Angiotensinogen promoter and angiotensinogen II receptor type 1 gene polymorphisms and incidence of ischemic stroke and neurologic phenotype in Fabry disease. (November 2013) - Altarescu, Gheona; Haim, Shimon; Elstein, Deborah
Abstract Context: Stroke and/or white matter lesions (WMLs) are significant in Fabry disease. Polymorphisms of angiotensinogen (AGT), AGT Promoter and angiotensinogen II receptor type 1 (AGTR1) are correlated with WMLs. Objectives: We compared AGT. AGT Promoter and AGTR1 genotypes to stroke incidence, Fabry-specific [Mainz Severity Score Index (MSSI)] severity score, and neurologic sub-score (n-MSSI). Methods: Sixty-three Fabry patients and 49 matched controls plus historic controls were genotyped. Institutional Review Board approval was received. Results. C and/or CC alleles of AGT Promoter and AGTR1 were significantly correlated with stroke and n-MSSI. Discussion/conclusion: Findings are suggestive of role of AGT Promoter and AGTR1 genotypes in Fabry phenotypes.